Abstract

No abstract available.

Full Article  |  PDF Article

References

  • View by:
  • |
  • |
  • |

  1. J. P. Duncan, P. G. Sabin, Exp. Mech. 5, 22 (1965).
    [CrossRef]
  2. S. Yokozeki, T. Suzuki, Japan. J. Appl. Phys. 9, 1011 (1970).
    [CrossRef]

1970 (1)

S. Yokozeki, T. Suzuki, Japan. J. Appl. Phys. 9, 1011 (1970).
[CrossRef]

1965 (1)

J. P. Duncan, P. G. Sabin, Exp. Mech. 5, 22 (1965).
[CrossRef]

Duncan, J. P.

J. P. Duncan, P. G. Sabin, Exp. Mech. 5, 22 (1965).
[CrossRef]

Sabin, P. G.

J. P. Duncan, P. G. Sabin, Exp. Mech. 5, 22 (1965).
[CrossRef]

Suzuki, T.

S. Yokozeki, T. Suzuki, Japan. J. Appl. Phys. 9, 1011 (1970).
[CrossRef]

Yokozeki, S.

S. Yokozeki, T. Suzuki, Japan. J. Appl. Phys. 9, 1011 (1970).
[CrossRef]

Exp. Mech. (1)

J. P. Duncan, P. G. Sabin, Exp. Mech. 5, 22 (1965).
[CrossRef]

Japan. J. Appl. Phys. (1)

S. Yokozeki, T. Suzuki, Japan. J. Appl. Phys. 9, 1011 (1970).
[CrossRef]

Cited By

OSA participates in CrossRef's Cited-By Linking service. Citing articles from OSA journals and other participating publishers are listed here.

Alert me when this article is cited.


Figures (2)

Fig. 1
Fig. 1

Orthogonal coordinate system for the analysis.

Fig. 2
Fig. 2

Experimental results: (a) interferogram of the glass slide by the Mach-Zehnder interferometer; (b) moiré pattern produced by two copies of interferogram; (c) fringe pattern without the glass slide; (d) moiré pattern obtained by the pattern of (a) and (c); (e) tracing of Fig. 2 (d); (f) moiré pattern between two copies of Fig. 2 (e).

Equations (9)

Equations on this page are rendered with MathJax. Learn more.

U ( x , y ) = A exp ( 2 π i / λ ) [ - θ x - g ( x , y ) ] + A exp [ ( 2 π i / λ ) θ x ] ,
I ( x , y ) = 2 A 2 { 1 + cos 2 π ( λ / 2 θ ) [ x + g ( x , y ) 2 θ ] } .
I ( x + a , y ) I ( x , y ) = 4 A 4 + 4 A 4 cos 2 π ( λ / 2 θ ) [ x + g ( x + a , y ) 2 θ + a ] + 4 A 4 cos 2 π ( λ / 2 θ ) [ x + g ( x , y ) 2 θ ] + 2 A 4 cos 2 π ( λ / 2 θ ) × [ 2 x + g ( x + a , y ) + g ( x , y ) 2 θ + a ] + 2 A 4 cos 2 π ( λ / 2 θ ) [ g ( x + a , y ) - g ( x , y ) 2 θ + a ] .
I ( x + a , y ) I ( x , y ) = 4 A 4 + 4 A 4 cos 2 π ( λ / 2 θ ) × [ x + g ( x , y ) 2 θ + a + a 2 θ g ( x , y ) x ] + 4 A 4 cos 2 π ( λ / 2 θ ) × [ x + g ( x , y ) 2 θ ] + 2 A 4 cos 2 π ( λ / 4 θ ) [ x + g ( x , y ) 2 θ + a 2 + a 4 θ g ( x , y ) x ] + 2 A 4 cos 2 π ( λ / 2 θ a ) [ 1 2 θ g ( x , y ) x + 1 ] .
I ( x + a , y ) I ( x , y ) = 4 A 4 + 2 A 4 cos 2 π ( λ / 2 a θ ) × [ 1 2 θ g ( x , y ) x + 1 ] .
g ( x , y ) / x = ( λ / a ) m - 2 θ ,
I ( x + a , u ) I ( x , y ) = 4 A 4 { 1 + cos [ 2 π λ g ( x + a , y ) ] } × { 1 + cos [ 2 π λ g ( x , y ) ] } 4 A 4 + 4 A 4 cos ( 2 π λ ) [ g ( x , y ) + a g ( x , y ) x ] + 4 A 4 cos ( 2 π λ ) g ( x , y ) + 2 A 4 cos 2 π ( λ / 2 ) [ g ( x , y ) + a 2 g ( x , y ) x ] + 2 A 4 cos [ 2 π ( λ / a ) g ( x , y ) x ] .
I ( x + a , y ) I ( x , y ) = 4 A 4 + 2 A 4 cos [ 2 π ( λ / a ) g ( x , y ) x ] .
g ( x , y ) / x = ( λ / a ) n ,

Metrics